Investigation of water content in electrolyte solution on electrochromic properties of WO3 thin Films - Zahra Abadi; Parvaneh Sangpour; ّFarbia Tajabadi; Benyamin Yarmand (Iranian Journal of Physics Research, 2017)
Tungsten oxide thin films were prepared by a cathodic electrodeposition method at -0.450 mV in order to investigate how water content affects their electrochromic properties. FESEM images exhibit that WO3 thin films consist of 65 nm uniform grains. Thin Films were electrochemically investigated in 0.1M LiClO4 in propylene carbonate electrolyte with and without 5vol% water content by cyclic voltammetry and chronoamperometry. The results indicate that tungsten oxide thin films exhibit faster switching time between coloration and bleaching states and also higher coloration efficiency in hydrated electrolyte.